ANALISIS KETIMPANGAN DISTRIBUSI PENDAPATAN DI KABUPATEN TAPANULI UTARA - Kijo Sinaga (Universitas Negeri Medan, 2013)
The distribution of income is related to the discrepancy of research aims to study the discrepancy level of income distribution at North Tapanuli Regency, to study the Kuznets hypothesis about “Reverse-U Curve”, to study the influence of economic growth rate, inflation and rate of open unemployment to the discrepancy level. Theresult of research indicates that the average percentage of the increasing of GRDP based on the basic price in North Tapanuli for 2000-2010 is 14,59 %. The average of inflation rate is high for 8,72. The average of open unemployment rate is 3,027 %. The Gini Ratio for North Tapanuli is less than 0,3. This indicates that the score less than 0,3 means the income is distributed evenly. The Reverse-U Curve because requirement of the square equation did not applied at North Tapanuli regency in 2000-2010. Based on estimation, the score of R2 is 0,336. F-calculated (0,336) is smaller than F-test (18,77) means that simultaneously the gross domestic product, inflation and the open unemployment rate did not influence the discrepancy of income distribution. The gross regional domestic product has not a significant influence to the discrepancy of income distribution at North Tapanuli regency. Inflation has not a significant influence to discrepancy of income distribution. The open unemployment rate has not a significant influence to the discrepancy of income distribution at North Tapanuli Utara Regency.